Does high-speed rail stimulate shareholder activism by small investors in China? - Qiong Wang; Kemin Wang (China Journal of Accounting Studies (CJAS), 2021)
This study investigates the effects of high-speed rail (HSR) introduction in China on small investors' on-site participation in shareholders' general meetings, which is used to measure the "inverse distance-participation syndrome". We find that HSR introductionhas a significantly positive effect on small investors' on-site attendance. The poorer the transportation infrastructure connecting other cities before HSR introduction, the shorter the distance between HSR station and the firm's headquarters after HSR introduction, and the more nonlocal investors the firm has, the higher the attendance rate. Small shareholder activism that arises with HSR introduction results in a higher likelihood of proposal rejection, fewer tunnelling by large shareholders, and less earnings manipulation. Overall, our results show that HSR introduction reduces monitoring costs for small shareholders and increases their on-site participation. Our findings provide important implications for policymakers on encouraging small shareholder activism.
Keywords: 650; High-speed rail; monitoring cost; shareholder meeting; small shareholder activism